2021
DOI: 10.1152/jn.00551.2020
|View full text |Cite
|
Sign up to set email alerts
|

State-dependent entrainment of cerebellar nuclear neurons to the local field potential during voluntary movements

Abstract: Understanding the relationship between the local field potential (LFP) and single neurons is essential if we are to understand network dynamics and the entrainment of neuronal activity. Here, we investigated the interaction between the LFP and single neurons recorded in the rat cerebellar nuclei (CN), which are part of the sensorimotor network, in freely moving rats. During movement, the LFP displayed persistent oscillations in the theta band frequency whereas CN neurons displayed intermittent oscillations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…We showed elsewhere that during voluntary movement, CN neurons tend to oscillate intermittently in the theta band frequency ( Baumel and Cohen, 2021 ; Baumel et al, 2021 ) and that the oscillation characteristics are significantly altered after the induction of body tremor by harmaline ( Baumel et al, 2021 ). Figures 2A–C shows example spectrograms and the corresponding power spectra of CN neurons that oscillated in the theta band frequency in the control ( Figure 2A ), Harm ( Figure 2B ), and Harm+NNC ( Figure 2C ) conditions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We showed elsewhere that during voluntary movement, CN neurons tend to oscillate intermittently in the theta band frequency ( Baumel and Cohen, 2021 ; Baumel et al, 2021 ) and that the oscillation characteristics are significantly altered after the induction of body tremor by harmaline ( Baumel et al, 2021 ). Figures 2A–C shows example spectrograms and the corresponding power spectra of CN neurons that oscillated in the theta band frequency in the control ( Figure 2A ), Harm ( Figure 2B ), and Harm+NNC ( Figure 2C ) conditions.…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that during voluntary movement, CN neurons display intermittent oscillations with a precise spectral structure ( Baumel and Cohen, 2021 ). This accurate spectral structure breaks down during the emergence of body tremor after harmaline administration ( Baumel et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also observed a ~7–8 Hz oscillations during pre-harmaline control conditions in motor thalamus LFP when rats were moving and not resting. A recent study by Baumel and Cohen ( 2021 ) demonstrated that a 7–8 Hz theta oscillation in the cerebellar nuclei was higher in power when the animals were moving compared to rest. Therefore, cerebellar output during movement may shape thalamic oscillations and may account for the intrinsic movement related cerebellar nuclear oscillations that we observed, although the functional relevance of this interaction is unknown.…”
Section: Discussionmentioning
confidence: 98%